Spectrophotometric method for hydroquinone determination in skin whitening creams / Nur Syamimi Zainudin and Nur Farehah Azhar - Zainudin, Nur Syamimi; Azhar, Nur Farehah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Hydroquinone belongs to the phenolic aromatic organic compound and is famously known as a skin whitening agent in cosmetic products. The presence of hydroquinone that exceeds the permitted level of 2 % in cosmetic products is toxic for humans. Therefore, a sensitive, accurate, simple, rapid and low-cost analytical method is required for hydroquinone determination. In this study, a spectrophotometric method has been proposed for the quantitative analysis of hydroquinone.